P‐ and S‐Wave Velocities of Exhumed Metasediments From the Alaskan Subduction Zone: Implications for the In Situ Conditions Along the Megathrust - Peter K. Miller; Demian M. Saffer; Geoffrey A. Abers; Donna J. Shillington; Anne Bécel; Jiyao Li; Charlotte Bate (Geophysical Research Letters)
Abstract The in situ state and properties of sediments entrained along subduction megathrusts exert key controls on their mechanics and slip behavior. Low seismic velocity and high Vp/Vs are hypothesized to indicate highly elevated fluid pressure, and are invoked as conditions in the source areas of slow earthquakes and tremor. We report on Vp and Vs measurements for exhumed metasediments from Kodiak Island, AK, representative of materials along the modern megathrust. Our data reveal anisotropy of ∼8–28% in Vp and ∼6.5–8% in Vs at effective stresses ranging from ∼1 to 90 MPa, with lower wavespeeds perpendicular to the dominant fabric. The fabric‐normal velocities are sufficiently low to explain observations from regional geophysical surveys and are consistent with rock physics‐based models that incorporate small (<1%) crack porosity. We suggest that low velocity at ∼8–20 km depth along megathrusts may arise simply from the presence of foliated metasediments, without requiring near‐lithostatic fluid pressure.